ANALISIS PENGEMBANGAN INDUSTRI KOMPONEN KAPAL DI DOK PANTAI LAMONGAN - Hidayat, Nasrul (Politeknik Negeri Madura, 2022)
Ship components industry has a very important role in shipbuilding industry development. It because the economic's scale of national shipbuilding industry has not been able to support this industry’s development. The Government's program to support the local ship production is an opportunity for the development of local ship parts industry, especially with the ship standardization policy. This paper is analyzing both the potential of ship components industry development based on the most affected factors using AHP (Analytical Hierarchy Process) method and the ship component industries development with case study of 750 DWT Pioneer Vessel. Based on the results of research, Hull Construction group of components has the most potential to develop which has the biggest cost weight percentage to total ship production cost. Hull Construction group of components is selected by the result of AHP analysis with considering the characteristics of the components and have the highest possibilities to develop the industries.